In vitro and in vivo thermal stress induces proliferation of Blastocystis sp. - Thergarajan, Gaythri; Govind, Suresh Kumar; Bhassu, Subha (Springer Verlag (Germany), 2018)
Blastocystis sp. is known to be the most commonly found intestinal protozoan parasite in human fecal surveys and has been incriminated to cause diarrhea and abdominal bloating. Binary fission has been widely accepted as the plausible mode of reproduction for this parasite. The present study demonstrates that subjecting the parasites in vitro to higher temperature shows the proliferation of parasite numbers in cultures. Transmission electron microscopy was used to compare the morphology of Blastocystis sp. subtype 3 isolated from a dengue patient having high fever (in vivo thermal stress) and Blastocystis sp. 3 maintained at 41 °C (in vitro thermal stress) and 37 °C (control). Fluorescence stains like acridine orange (AO) and 4′,6′-diamino-2-phenylindole (DAPI) were used to demonstrate the viability and nuclear content of the parasite for both the in vitro and in vivo thermal stress groups of parasites. Blastocystis sp. at 37 °C was found to be mostly vacuolar whereas the in vitro thermal stressed isolates at 41 °C were granular with electron dense material seen to protect the granules within the central body. Parasites of the in vivo thermal stressed group showed similar ultrastructure as the in vitro ones. AO and DAPI staining provided evidence that these granules are viable which develop into progenies of Blastocystis sp. These granular forms were then observed to rupture and release progenies from the mother cells whilst the peripheral cytoplasmic walls were seen to degrade. Upon exposure to high temperature both in vitro and in vivo, Blastocystis sp. in cultures show higher number of granular forms seen to be protected by the electron dense material within the central body possibly acting as a protective mechanism. This is possibly to ensure the ability to survive for the granules to be developed as viable progenies for release into the host system.